(untitled) (Journal of Atomic and Molecular Sciences, 2022)
Time-dependent density functional theory (TDDFT) method has been performed to investigate the properties of N_1-H_1… O_1 hydrogen bond of N-methylaniline-DMSO complex (complex I) and N-methylaniline-acetone complex (complex II) in the excited state. The infrared spectra are in good agreement with the experiment data. The analysis of the bond length and AIM (atoms in molecules) demonstrated that the N_1-H_1… O_1 hydrogen bond is weakening from DMSO to acetone in the ground state. That is to say, the intermolecular hydrogen bond N_1-H_1 … O_1 between N-methylaniline and solvent molecular is stronger with the polarity of solvent stronger. Upon photoexcitation, the analysis of AIM implies that the intermolecular complex II is enhanced. Interestingly, the hydrogen bond N_1-H_1… O_1 of complex I is weakened. The analysis of molecular orbital also support the results that the intermolecular hydrogen bond N_1-H_1 … O_1 of complex I is weakened whereas it of complex II is enhanced.